Concentrating Mill Wastes are the Source of Pollution of Human Environment and Natural Ecosystems with Heavy Metals: A Case Study in Primorsky Krai, Russian Federation - Irina A. Tarasenko; Alexander V. Zin’kov; Aleksei S. Kholodov; Muhammad Riaz; Valeriy I. Petukhov; Nikita Y. Popov; Aristidis Tsatsakis; Kirill S. Golokhvast (Journal of Chemistry)
Elevated contents of hazardous elements in natural ecosystems are often associated with human activities. Significant quantities of these elements, including heavy metals, are concentrated in tailings. The goal of the study was to assess the mineralogical and geochemical features of the old tailings of the decommissioned Krasnorechenskaya concentrating mill (located in Primorsky Krai, Russian Federation), which was processing complex tin-polymetallic and silver-lead-zinc ores, the chemical features of tailings pond waters, and the extent of environmental impact on the nearby Rudnaya river. In addition to the analysis of rock and water samples, the software modeling of the water-rock-gas system was carried out. In the study area, the minerals and rocks undergo changes that lead to the formation of highly mineralized, acidic waters saturated with various elements. In the tailings ponds, the maximum permissible concentrations were exceeded for Zn, Cd, Cu, Mg, Fetotal, Pb, Mn, Al, As, Co, Be, Sr, Ni, and Ba. The drainage from the tailings pond tripled the total mineralization of the Rudnaya river relative to the background values. However, the intoxication of the ecosystem by tailing products is partially inhibited by the secondary minerals in the tailings ponds. The negative impact is of a local nature, and 500 m downstream the concentration of many of the above elements is reduced. Despite this, the system that forms the chemical composition of highly mineralized waters is far from the equilibrium state. The oxidation of sulfides, dissolution of other minerals, and migration of oxidation and hydrolysis products will continue affecting the environment. In this regard, it is necessary to conduct environmental monitoring and undertake activities aimed at the recovery of mature concentration tailings or at suppressing the activity of hazardous elements by the conservation of tailings ponds.